The Logit as a Model of Product Differentiation: Further Results and Extensions - Simon P. Anderson; Andre de Palma (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1989)
There is a growing interest in using the discrete choice approach to study oligopolistic competition under product differentiation, and a prominent discrete choic model is the multinomial logit. Here we analyze various aspects of the logit in this context. We first show that the predictions of the logit are very similar to those of the well-known CES model and explain why this is so. We next discuss the existence and the uniqueness of a price equilibrium for a general version of the logit. We illustrate (using the logit) the flexibility and tractability of the discrete choic approach for two diferent problems. The first of these finds a free-entry equlibrium with multiproduct firms. The second uses the logit to construct a simple search model. We also introduce the nested logit as an oligopoly model and apply it to these two problems.
Keywords: O22; 330; Discrete choice model; CES model oligopolistic competition; multiple product firms; nested logit model